Protein modification regulated autophagy in Bombyx mori and Drosophila melanogaster - Wu, Wenmei; Lin, Luobin; Zhao, Yuntao; Li, Huaqin; Zhang, Rongxin (Frontiers in Physiology, 2023)
Post-translational modifications refer to the chemical alterations of proteins following their biosynthesis, leading to changes in protein properties. These modifications, which encompass acetylation, phosphorylation, methylation, SUMOylation, ubiquitination, and others, are pivotal in a myriad of cellular functions. Macroautophagy, also known as autophagy, is a major degradation of intracellular components to cope with stress conditions and strictly regulated by nutrient depletion, insulin signaling and energy production in mammals. Intriguingly, in insects, 20-hydroxyecdysone signaling predominantly stimulates the expression of most autophagy-related genes while concurrently inhibiting mTOR activity, thereby initiating autophagy. In this review, we will briefly outline post-translational modifications regulated autophagy in insects, including Bombyx mori, and Drosophila melanogaster. A more profound understanding of the biological significance of posttranslational modifications in autophagy machinery not only unveils novel opportunities for autophagy intervention strategies, but also illuminates their potential roles in development, cell differentiation, as well as the process of learning and memory processes in both insects and mammals.